Green Innovation and Sustainable Business Practices: Evidence from Indonesian Manufacturing Firms - Saad Yousfi; Fatima Ezzahra Lamrani; Samira El Yassini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
As environmental concerns grow, companies are increasingly adopting green innovation and sustainable business practices to meet both regulatory requirements and consumer demand. This paper investigates the drivers of green innovation in Indonesian manufacturing firms and assesses its impact on environmental performance. Using survey data from 100 firms, the study finds that government incentives and consumer pressure significantly influence companies' sustainability strategies. However, the research also identifies challenges in implementing sustainable practices, particularly related to costs and limited technical knowledge. Policy implications include strengthening incentives for green technology and creating partnerships for knowledge sharing.